2009
DOI: 10.1111/j.1365-2095.2008.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein requirement for maintenance and maximum growth of two-banded seabream (Diplodus vulgaris) juveniles

Abstract: The effects of various dietary protein levels on growth performance, whole body composition and nutrient utilization were studied in two-banded sea bream (Diplodus vulgaris), a candidate species for aquaculture. Fish (initial weight 6.1 g) were fed to satiety six iso-energetic diets, containing 5%, 12.5%, 25%, 35%, 45% or 55% of crude protein during 72 days. Fish fed 35% and 45% protein attained better growth and feed utilization than the other groups (P < 0.05). Daily growth index and feed conversion ratio we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 43 publications
7
57
3
3
Order By: Relevance
“…in dietary protein levels produces an increase in average weight and nal length, FCF, AWG, DWG, and K until reaching maximum values with the 50% protein diet, with a direct correlation between growth and the amount of protein in the diet, which has been reported for various sh species (Santigosa et al 2011a, Prasad 2014, while an excess of proteins in the diet can stimulate increased trypsin production, which increases both satiety and energy costs used for ammonia excretion. Therefore, an increase in protein catabolism reduces the use of other nutrients (carbohydrates and lipids) as an energy source, due to deamination, which causes greater feed intake and low protein utilization (Morgane and www.ujat.mx/era Fountoulaki 2014), while a greater release of amino acids causes a greater concentration of ammonia in the plasma, which can be toxic (Ozório et al 2009), and reduces growth (Mohseni et al 2013) and PER, as has been seen in the leopard coral grouper (Plectropomus leopardus, Lacepede, 1802) and the Yellow cat sh (Horabargus brachysoma, Günther, 1864) (Prasad 2014, Xia et al 2015. In this same aspect, the high PER values in diets with low protein percentages are usually due to the u-pregulation of amino acid transport as a response to the compensation for a nutritional de cit in the diet (Santigosa et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…in dietary protein levels produces an increase in average weight and nal length, FCF, AWG, DWG, and K until reaching maximum values with the 50% protein diet, with a direct correlation between growth and the amount of protein in the diet, which has been reported for various sh species (Santigosa et al 2011a, Prasad 2014, while an excess of proteins in the diet can stimulate increased trypsin production, which increases both satiety and energy costs used for ammonia excretion. Therefore, an increase in protein catabolism reduces the use of other nutrients (carbohydrates and lipids) as an energy source, due to deamination, which causes greater feed intake and low protein utilization (Morgane and www.ujat.mx/era Fountoulaki 2014), while a greater release of amino acids causes a greater concentration of ammonia in the plasma, which can be toxic (Ozório et al 2009), and reduces growth (Mohseni et al 2013) and PER, as has been seen in the leopard coral grouper (Plectropomus leopardus, Lacepede, 1802) and the Yellow cat sh (Horabargus brachysoma, Günther, 1864) (Prasad 2014, Xia et al 2015. In this same aspect, the high PER values in diets with low protein percentages are usually due to the u-pregulation of amino acid transport as a response to the compensation for a nutritional de cit in the diet (Santigosa et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in the present study for salema porgy, Sá et al [21] and Coutinho [22] also reported other sparid candidates such as white seabream (Diplodus sargus) (0.89%/day) and zebra seabream (Diplodus cervinus) (0.8%/day) as slow growing marine species, respectively. On the other hand, higher SGRs of 1.22%/day [23] and 1.54%/day [24] were recorded for two-banded seabream (Diplodus vulgaris) and sharpsnout seabream (Diplodus puntazzo), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tingkat konsumsi pakan harian (KPH) dihitung berdasarkan formula (Ozorio et al, 2009): Rasio konversi pakan (FCR) (Unnikrishnan & Paulraj, 2010):…”
Section: Perhitungan Respons Pertumbuhan Dan Pemanfaatan Pakan Ujiunclassified